The Difference between Cartilaginous and Bony Sulcus Angles for Patients with or without Patellofemoral Instability: A Systematic Review and Meta-Analysis - Tan, Si Heng Sharon; Chng, Kiat Soon Jason; Lim, Beatrice Ying; Wong, Keng Lin; Doshi, Chintan; Lim, Andrew Kean Seng; Hui, James Hoipo (The Journal of Knee Surgery, 2020)
The cartilaginous sulcus angle and bony sulcus angle have been widely used to evaluate trochlea dysplasia. The current review aims to evaluate (1) whether there is a difference in measurement for cartilaginous and bony sulcus angles, (2) whether both the cartilaginous and bony sulcus angles could be used to differentiate between patients with or without trochlear dysplasia, and (3) whether the same cut-off of 145 degrees, originally used for radiographs, can be applied for the cartilaginous and bony sulcus angles measured on CT and MRI. The review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRSIMA) guidelines. A total of 11 publications with 1204 patients were included. All publications reported the sulcus angle to be greater in patients with patellofemoral instability. All publications reported the cartilaginous sulcus angle to be greater than the bony sulcus angle (MD 7.27 degrees; 95% CI: 5.67 – 8.87). The mean cartilaginous sulcus angle for the control group was 141.83 degrees (95% CI: 139.90 – 143.76) while the mean cartilaginous sulcus angle for patients with patellofemoral instability was 156.24 degrees (95% CI: 153.71 – 158.77). The mean bony sulcus angle for the control group was noted to be 133.69 degrees (95% CI: 131.23 – 136.15) while the mean bony sulcus angle for patients with patellofemoral instability was 148.42 (95% CI: 144.02 – 152.82). Both the cartilaginous and bony sulcus angles measured on CT and MRI could therefore be used to differentiate between patients with and without trochlear dysplasia. However, the cartilaginous sulcus angles are significantly higher than that of bony sulcus angles. Different cut off values should therefore be used.
Keywords: patellar instability; patellofemoral instability; trochlear dysplasia; sulcus angle; trochlear angle; cartilaginous; bony